Adição de desinfetantes na água de bebida durante o jejum pré-abate de frangos de corte: microbiologia e morfologia do trato gastrintestinal - Barreiro, Fabiana Ribeiro [UNESP] (2015)
The objective of this experiment was to test whether the addition of disinfectants approved for use in food industry to broiler drinking water during pre-slaughter feed withdrawal period was efficient in reducing the quantities of microorganisms, such as Escherichia coli and Enterococci, in broiler crops and ceca. Reduction of these microorganisms would likely also reduce pathogenesis post-slaughterhouse. It was also investigated if these disinfectants caused some intestinal damage that could lead to dissemination of microorganisms to the carcass. A total of 60 Cobb male broilers were distributed in pens according to the treatments. The preslaughter period was 12 hours and the disinfectants added to water during this period were based on iodine, quaternary ammonium, biguanide, and peracetic acid. Samples of crop and cecal content were collected for microbiological analysis; and duodenum and jejunum for histological analysis. The conclusion was that preslaughter feed withdrawal should be coupled with methods for crop disinfection. Disinfectants based on iodine, quaternary ammonium and peracetic acid did not present satisfactory results for use in broiler drinking water to decrease the microorganism populations from crop. Biguanide-based disinfectant, in association with preslaughter feed withdrawal, reduced the enterococci amount from crop. However, the recommendation of its addition to broiler drinking water must be done with caution, because cecal content presented higher quantities of E. coli when biguanide was used. Peracetic-acid based disinfectant promoted intestinal villi integrity when associated to preslaughter feed withdrawal, decreasing the risk of dissemination of pathogenic microorganisms from intestinal content to the carcass